PENGARUH LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PADA PESERTA DIDIK DI SMK NEGERI PAKU KECAMATAN BINUANG KABUPATEN POLEWALI MANDAR - Abdul Latief (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2014)
This study aimed to determine the influence of School Environment toward Civic Education Learning Result of Students at SMK Paku, Binuang Sub-district. The sample subject/ object of this study were 55 students. This study employed influence research (causal). Technique of collecting data was gathered by the results of documentation and by giving questionnaires to the respondents. The data was analyzed by using descriptive analysis method and inferential analysis method. The results of descriptive analysis method illustrated that the influence of the school environment obtained an average score was 34.37, which is the medium category, and learning result of Civic Education obtained the average value was 82.37 at the high category. Moreover, the results of inferential analysis method suggested that there was an influence of the school environment toward Civic Education learning result for the students at SMK Paku, Binuang Sub-district.